ALK expression in extranodal anaplastic large cell lymphoma favours systemic disease with (primary) nodal involvement and a good prognosis and occurs before dissemination. Issue 6 (1st June 2000) - Berge, Rosita L ten; Oudejans, Joost J; Ossenkoppele, Gert-Jan; Pulford, Karen; Willemze, Rein; Falini, Brunangelo; Chott, Andreas; Meijer, Chris J L M
Abstract : Aims —In anaplastic large cell lymphoma (ALCL), the site of origin has been described as an important prognostic factor. Recently, a fusion protein containing anaplastic lymphoma kinase (ALK) was described in systemic nodal ALCL, and shown to be associated with a good prognosis. The aims of this study were to investigate whether the presence of ALK protein differs between ALCL of different sites of origin; to determine whether ALK expression occurs before dissemination to other sites; and, finally, to investigate whether the site of origin remains a prognostic parameter in ALK negative ALCL. Methods —ALK expression, as detected by immunohistochemistry using the monoclonal antibodies ALK1 and ALKc, was studied in 85 ALCLs from different sites of origin. In 22 patients, ALK expression was studied in multiple biopsies from different sites (including 13 skin, 16 lymph node, and nine other). Overall survival time was analysed using the Kaplan Meier method. Results— ALK expression was found in 20 of 51 systemic ALCLs with (primary) nodal involvement. No ALK expression was found in 15 primary cutaneous, 14 gastrointestinal, and five nasal ALCLs. Multiple and subsequent biopsies of patients showed ALK expression to be identical to that seen in the primary diagnostic biopsy. Kaplan Meier survival curves showed that in ALK negative ALCLs originating from different sites, primary cutaneous cases are associated with an excellent overall survival, whereas the other cases show a comparable five years survival of less than 40%. Conclusions —If present, ALK expression favours systemic ALCL with (primary) nodal involvement, and can be used in differentiating between extranodal involvement of systemic (nodal) ALCL and primary extranodal ALCL. ALK is expressed consistently in multiple biopsies of a given patient, indicating that the chromosomal abnormality leading to aberrant ALK expression occurs before dissemination to other sites. Finally, in ALK negative non-cutaneous ALCLs, different sites of origin show comparable poor survival.